ChemInform Abstract: Preparation, Ionic Conductivity and Thermochemistry of New Bi12.5Lu1.5ReO24.5 Phase. Issue 52 (24th December 2013) - Matskevich, N. I.; Wolf, Th.; Greaves, C.; Bryzgalova, A. N.
Abstract The new title compound is synthesized from a mixture of Bi2O3, Re2O7, and Lu2O3 in air (1070 K, 70 h) and characterized by powder X‐ray and neutron diffraction, conductivity measurements, and solution calorimetry.